REINTEGRATING PRODUCTIVE ACTIVITIES IN URBAN SPACES: A COMPARATIVE ANALYSIS OF STRATEGIC URBAN PLANNING IN BRUSSELS AND VIENNA - Narimene Boutemine; Meriem Chabou-Othmani (International Journal of Innovative Technologies in Social Science, 2024)
Since the 2007 financial crisis, the strategic role of industrial manufacturing in urban economies has been increasingly recognized in the United States and Europe. The concept of the productive city represent a new vision for urban development that integrates living and production spaces. The integration of productive activities into urban areas poses a significant challenges, but also offers opportunities to foster more resilient and sustainable urban models. This paper examines the urban and economic policies implemented in two European cities, Brussels and Vienna, by conducting a comparative analysis as a research method, with a focus on the types of activities defined by urban production and the spatial perspective. The findings of our analysis enabled us to develop recommendations for public authorities concerning the implementation of the productive city. Our results further illustrate that the productive city is not solely determined by the spatial distribution or classification of activities; rather, it represents a strategic approach aimed at establishing a development framework responsive to the specific economic dynamics of each context. Achieving this requires a clear articulation of objectives, the deployment of suitable regulatory instruments, and the adoption of participatory governance mechanisms.